Distribution of Productivity among Authors in Potato Research (1900-1980) - Gupta, B. M.; Kumar, Suresh; Syed, Shaheen; Singh, Karan Vir (Journal of Information and Knowledge, 1996)
Scientific productivity is measured in terms of publication in various forms. This paper presents: (1) author productivity patterns of Indian Potato Research for the period 1900-1980, and (2) application of Lotkas Law in its different forms.